Responses on the Three Factor Eating Questionnaire Restraint and Disinhibition Scales Change After a Controlled Energy-Restricted Diet (P21-002-19) - Leon, Angela De (Curr Dev Nutr, 2019)
OBJECTIVES: The Three Factor Eating Questionnaire (TFEQ) is a validated psychometric tool widely used in nutrition research. The TFEQ measures three constructs related to human eating behavior (cognitive restraint of eating, disinhibition, and perceived hunger) and is typically used to identify “fixed” traits associated with obesity. Although inconsistent, evidence suggests that these constructs may be modifiable with diet and weight loss. We sought to determine the mutability of each TFEQ construct in response to a controlled energy-restricted diet in overweight and obese women. METHODS: Healthy overweight and obese women aged 20–44 (N = 19) were provided with all foods for daily consumption at a level of 20% reduction of usual energy intake for a period of 8 weeks. Study food was packaged as separate meals representing breakfast, lunch, and dinner. Participants were instructed to consume all foods together as separate meals and between-meal snacking was prohibited. Body weight was measured at baseline and then weekly during the intervention. The TFEQ was administered at baseline and at the end of the 8-week controlled feeding. Differences in scores for each factor of the TFEQ were analyzed using paired t-tests. Results are presented as means ± SD. RESULTS: On average, participants lost 3.8 ± 1.7 kg. TFEQ restraint scores were greater at the end of week 8 (12.3 ± 4.5) compared to baseline (8.2 ± 4.4), t(18) = 4.00, P < 0.001. Conversely, TFEQ disinhibition scores were lower at week 8 (6.9 ± 3.4) compared to baseline (9.5 ± 2.6), t(18) = 3.42, P = 0.003. Though not significantly different, TFEQ hunger scores were greater at baseline (6.7 ± 3.3) compared to week 8 (5.2 ± 3.4) despite 8 weeks of weight loss. Changes in TFEQ scores did not correlate with change in body weight. CONCLUSIONS: These results suggest that dietary restriction aimed at eliminating between-meal snacking increases cognitive restraint of eating and decreases disinhibition, independent of weight loss. Additionally, the conscious intention of adhering to eating only 3 meals a day may have improved the perception of hunger cues while reducing susceptibility to external food cues. These attitudinal and behavioral changes are important for adherence to a healthy eating pattern. FUNDING SOURCES: United States Department of Agriculture, Agricultural Research Service #3062-51000-051-00D and the North Dakota Beef Commission.